2018
DOI: 10.1186/s12929-018-0455-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 receptor (ST2) deficiency downregulates myeloid precursors, inflammatory NK and dendritic cells in early phase of sepsis

Abstract: BackgroundSepsis is a life-threatening disease mediated by profound disturbances in systemic inflammatory response to infection. IL-33 is multifunctional regulator of numerous aspects of innate and adaptive immune response. The aim of this article was to further evaluate the role of IL-33 receptor (ST2) in different pathways of innate immunity during early polymicrobial sepsis.MethodsPolymicrobial sepsis was induced using cecal ligation and puncture (CLP) model in ST2 deficient (ST2−/−) and wild type BALB/c mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…One group reported that the administration of IL-33 actually enhanced the production of IL-17 while decreasing the levels of IL-6, IL-10, and IFNγ following CLP (41). Similarly, another group found that the deletion of the IL-33 receptor ST2 led to a reduction in the frequency and number of IL-17 producing NK cells after CLP (86). However, a recent study of human patients with Staphylococcus aureus bacteremia revealed that a higher ratio of Th17 to Th1 cytokines early after sepsis onset was associated with increased mortality (49).…”
Section: Interactions Between Il-17 Il-27 and Il-33mentioning
confidence: 90%
See 1 more Smart Citation
“…One group reported that the administration of IL-33 actually enhanced the production of IL-17 while decreasing the levels of IL-6, IL-10, and IFNγ following CLP (41). Similarly, another group found that the deletion of the IL-33 receptor ST2 led to a reduction in the frequency and number of IL-17 producing NK cells after CLP (86). However, a recent study of human patients with Staphylococcus aureus bacteremia revealed that a higher ratio of Th17 to Th1 cytokines early after sepsis onset was associated with increased mortality (49).…”
Section: Interactions Between Il-17 Il-27 and Il-33mentioning
confidence: 90%
“…The ability of IL-33 to improve survival during sepsis is linked to the rescue of neutrophil migration to the site of infection (40), to improvements in bacterial clearance, and to a reduction in lymphocyte apoptosis (41). IL-33 also suppresses the inflammatory response by a variety of innate lymphocytes (86) and modulates the activity of ILC2 cells (4749). In addition to direct effects on other lymphocytes, IL-33 impacts the activity of other cytokines, including IL-17 (41, 87).…”
Section: Introduction To Sepsis and The Il-17/il-27/il-33 Axismentioning
confidence: 99%
“…The pathway has been implicated in multiple inflammatory disorders including asthma, 38 chronic obstructive pulmonary disease, 39 and inflammatory bowel disease 40 and vascular disease including acute myocardial infarction 41,42 and heart failure. 43 Studies into the mechanism of ST2-IL33 action initially focused on T lymphocytes, 44-46 but more recent data implicate the system in the regulation of innate immune components including NK cells 47-49 and macrophages. 50 The current study supplements these findings with further evidence for a role of sST2 in modifying the NK and monocyte response to IPH.…”
Section: Discussionmentioning
confidence: 99%
“…We used a CLP-induced mouse model of sepsis. Studies have shown that in addition to lung inflammatory damage, CLP-induced model animals also produce organ damage and the rise of pro-inflammatory cytokines in the myocardium, liver, spleen, kidney, and digestive tract (25)(26)(27)(28)(29)(30)(31). From the perspective of pathogenesis, the causes that induce sepsis and subsequent organ damage include inflammatory response disorder, immune dysfunction, mitochondrial damage, coagulation dysfunction, neuroendocrine-immune network abnormality, endoplasmic reticulum stress, and autophagy (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%